Humbug! : The Politics of Art Criticism in New York City's Penny Press - Katz, Wendy Jean (Book collections on Project MUSE., 2020)
Mines the more than 300 newspapers published in New York City before the Civil War for art criticism, in order to trace the changing political positions of artists, artworks, and authors.